"Let me comment on your video" - supporting personalized end-user comments within third-party online videos. - Guimarães, Rodrigo Laiola; Cesar, Pablo; Bulterman, Dick C. A. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
Long before the first transmission in color of a World Cup in 1970, people used to gather around the few existing radio and TV sets to watch together and talk about their favorite programs. Decades later, not only the technology has significantly changed but also people's consumption and commenting habits. Nowadays, one can easily watch an online video on demand and share comments with others asynchronously. However, current video commenting facilities do not take into account the temporal nature of videos. Viewers can only add comments that will then appear statically underneath the video. Motivated by a survey research on current media watching and commenting practices, we report on our findings from the evaluation of an online video commenting system that allows users to add synchronized comments to third-party videos. Our results indicate that users appreciate the functionalities of our system and find it better to comment when compared to existing tools. Ultimately, we hope that our work can bring insights to be considered in the design of next generation online video commenting tools.